Miscibility of blends of poly(methyl methacrylate) and oligodiols based on a bisphenol A nucleus and ethylene oxide or propylene oxide branches - Jaffrennou, B. (2004)
Cloud-point curves of blends of poly(methyl methacrylate) (PMMA) with a series of oligodiols based on a bisphenol A nucleus and short branches of poly(ethylene oxide) or poly(propylene oxide) (BPA-EO or BPA-PO), and with PEO and PPO oligomers, were obtained using a light transmission device. Experimental results were fitted with the Flory–Huggins model using an interaction parameter depending on both temperature and composition. For PMMA/PEO and PMMA/PPO blends, the miscibility increased when increasing the size of the diol, due to the significant decrease in the entropic and enthalpic terms contributing to the interaction parameter. This reflected the decrease in the self-association of solvent molecules and in the contribution of terminal OH groups to the mismatching of solubility parameters. For PMMA/BPA-EO blends, a decrease of the entropic contribution to the interaction parameter when increasing the size of the oligodiol was also found. However, the effect was counterbalanced by the opposite contribution of combinatorial terms leading to cloud-point curves located in approximately the same temperature range. For PMMA/BPA-PO blends, the interaction parameter exhibited a very low value. In this case, the effect of solvent size was much more important on combinatorial terms than on the interaction parameter, leading to an increase in miscibility when decreasing the oligodiol size. For short BPA-PO oligodiols no phase separation was observed. The entropic contribution of the interaction parameter exhibited an inverse relationship with the size of the oligodiols, independent of the nature of the chains bearing the hydroxyls and the type of OH groups (primary or secondary). This indicates that the degree of self-association of solvent molecules through their OH terminal groups, was mainly determined by their relative sizes.